Pendampingan Pertolongan Pertama Bagi Masyarakat Korban Banjir Di Kota Pekalongan - Hendri Hermawan Adinugraha (Institut Riset dan Publikasi Indonesia (IRPI), 2021)
Activities to anticipate natural disaster management through first aid assistance for flood victims in Pekalongan City are very applicable and needed by flood-affected communities. So that the urgency of first aid in health service efforts for flood victims in Pekalongan City cannot be doubted. This community service aims to describe the form of first aid assistance for flood victims in Pekalongan City. This community service method is carried out through several stages, namely planning and preparation, implementation, and evaluation of activities. The results of this service show that first aid assistance for flood victims in Pekalongan City has been carried out by the community service team together with UKK-KSR PMI Unit IAIN Pekalongan. Planning and preparation before undertaking a community service program. The implementation of the community service program which consists of several activities, namely mental recovery of children affected by flooding, conducting basic tension medical treatment to residents affected by the flood, distributing aid to refugee camps for flood victims, conducting assessments in refugee camps, and evacuating flood victims. Finally, the process of evaluation and improvement for further service activities.